Tanggung Jawab Notaris Terhadap Surat Wasiat yang Berindikasi Palsu - Zar, Mufti Muadil; Umar; Qodri, M. Amin (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2023)
The purpose of this study is to find out and analyze how the Notary's responsibility for the alleged crime of forgery in an authentic deed based on Decision Number: 1398/Pdt.G/2017/PA.JP. And to find out and analyze how the legal consequences of a will made by a notary are contrary to the applicable legal system. Using the theory of legal certainty, the theory of authority, the theory of responsibility, and the theory of the strength of authentic deed proof. Normative juridical research methods. The approach used is a conceptual approach, statutory approach and legal case approach. The results of this study, against a notary who is proven to have made a deed that is suspected of having a criminal element, needs to be seen first from the factors of error and intentionality, so that a notary who is consciously involved on purpose or is involved in making a fake authentic deed if it is proven legally and convincingly true, then the notary can be subject to criminal sanctions, with the alleged criminal act of forgery committed by a Notary, criminal law accountability will be held. Meanwhile, if the elements of the error are not fulfilled, the Notary cannot be punished. The legal consequence of an authentic testament made by a Notary who commits an unlawful act for negligence in making the deed is the loss of the authenticity of the deed and it becomes an underhanded deed and the authentic deed can be canceled if the party who argues can prove it in a trial in court , because the making of an authentic deed must contain outward, formal, and material elements, or one of these elements is incorrect and gives rise to criminal or civil cases which can then be proven untrue.